STRATEGI KOMUNIKASI DINAS KEBUDAYAAN DAN PARIWISATA KABUPATEN KUANTAN SINGINGI DALAM MENGEMBANGKAN BRAND DESTINATION PACU JALUR - Meitaliza, Yeli; Awza, Rusmadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Kuantan Singingi regency is an area rich in culture and tradition one of which is the pathway. Inter-regional tourism competition is increasingly competitive in recent years, to be able to compete required an effective strategy to develop the potential and uniqueness of the region in order to compete with other regions. For that need to strengthen the identity of a destination or better known as the destination brand. Brand destination is considered to be the right strategy to be run by the Culture and Tourism Office of Kuantan Singingi Regency to develop existing tourism and attract the attention of local tourists and foreign tourists to come to Kuantan Singingi Regency. This study aims to determine the communication strategy of Culture and Tourism Office of Kuantan Singingi Regency in establishing the brand destination of pacu jalur. The research method used in this research is qualitative research method. This qualitative research aims to explain the deep phenomenon through interview data collection techniques, observation and documentation. Using purposive techniques by interviewing 5 informants and using accidental techniques to interview the community. The results of this study is to determine the audience in advance of the identification of local tourists and foreign tourists. The communicator of this destination brand is the Culture and Tourism Office of Kuantan Singingi Regency for communicators in Jakarta as a form of launching effort conducted by the Head of Culture and Tourism Office of Kuantan Singingi Regency. The message strategy used is persuasive and informative which is packed very interesting and includes logo along with tagline. The use of media used by the Office of Culture and Tourism Kuantan Singingi Regency in developing brand destination Pacu Jalur through electronic media, print media, online media and print media campaigns such as banners and billboards. The effect of this brand destination can make people and tourists visit pacu jalur so it can help raise PAD..